Efeito do período de jejum na fase final de criação de frangos de corte machos sobre rendimento e composição da carcaça - Sartori, José Roberto; Gonzales, Elisabeth [UNESP]; De Souza, Eduardo Mendonça; Garcia, Edvaldo Antônio [UNESP]; Wechsler, Francisco Stefano [UNESP] (My University, 1997)
The objective of this work was to evaluate the effect of fasting period in the last growing phase on carcass yield and composition of male broilers. Two thousand one-day old male chicks were distributed in five randomized blocks according to a 4×2 factorial (four feeding programs (P): ad libitum or one of three fasting schedules: 8-12, 12-16 and 8-16; and two strains (S): Ross or Hubbard-Peterson. Fifty birds were used per replicate. Birds were raised under identical feed and management conditions until day 42. The fasting schedules were applied from day 43 to day 56. At day 56, five birds per replicate were randomly sampled, weighed, slaughtered, eviscerated, dry-cooled, cut and deboned. No effects of P or SxP interaction were observed for carcass characteristics. The Ross (R) broilers showed higher weight, and yields of breast meat, leg meat and abdominal fat than the Hubbard-Peterson (H) birds, which showed higher weights and yields of head plus neck, feet, leg bones and wings. The ad libitum birds showed higher crude protein in thigh meat than those submitted to the 8-12 h fast. A SxP interaction was observed for meat ash content. The R broilers showed higher ash content in breast and thigh meat than the H birds in the 8-12 h fast treatment. On the other hand, the R broilers submitted to the 8-12 h fast showed higher ash contents in breast and thigh meat than birds from the same strain in the other feeding programs. Fasting in the last phase of rearing did not alter the yield of whole carcass, carcass cuts and abdominal fat, but morning fast influenced carcass chemical composition.
The effect of fasting period in the last phase of rearing on carcass yield and composition of male broilers
Keywords: Broilers; Carcass composition; Carcass yield; Fasting; Heat stress